„Uprzejmie donoszę” — metody pracy tajnych informatorów wobec kleru katolickiego w okresie Polskiej Rzeczypospolitej Ludowej na terenie Dolnego Śląska - Edyta Włodarczyk-Czech (Wrocławsko-Lwowskie Zeszyty Prawnicze)
Among all the organisations operating in the Polish People’s Republic, religious associations — which were guided by a doctrine completely different from the Marxist-Leninist thought propagated at the time — were particularly important for the communists. Hence, the Catholic Church, as the largest church in Poland, was of interest to the Security Service throughout the entire period of the Polish People’s Republic.